Scouting the Efficacy of Chitosan-coated Litsea Lipid Carriers Nanoplatform as an Oral Delivery System of Lornoxicam in an Inflammatory Animal Model - Walaa A. El-Dakroury; Abdelrahman R. Said; Gihan F. Asaad; Heba M. I. Abdallah; Marwa E. Shabana; Rahma A. Abdelsalam; Eman M. Elsadek; Basma H. Mohamed; Yara S. Mohamed; Sara M. Seliem; Elsayed Y. Hamada; Belal W. Attef; et al. (Journal of Pharmaceutical Innovation, 2026)
Lornoxicam-loaded chitosan-coated Litsea lipid nanocarriers (LRX-CS-LLCs) were developed as an innovative oral delivery system, combining the synergistic anti-inflammatory effects of Litsea cubeba oil with the mucoadhesive properties of chitosan. The GC/MS analysis of Litsea cubeba oil identified α -citral (47.56%), β -citral (26.86%), and D -limonene (14.00%). Various LRX-loaded LLCs were prepared and optimized. Fourier transform-infrared (FTIR) and differential scanning calorimetry (DSC) confirmed its structural integrity. The optimized (LRX-CS-LLCs) exhibited a particle size of 165.4 ± 6.3 nm, zeta potential of + 26.3 ± 3.2 mV, and entrapment effectiveness of 98.2%. In vitro release followed a controlled kinetic profile. In vivo, LRX-CS-LLCs significantly reduced carrageenan-induced paw edema (77 ± 1.86% inhibition) and PGE2, COX-2, and TNF-α levels by 4.4-, 3.6-, and 3-fold, respectively, compared to the positive control group. Histopathological examinations confirmed normal tissue architecture. Notably, LRX-CS-LLCs outperformed pure-LRX, marketed-LRX, and uncoated-LRX-LLCs, emphasizing its promise as an effective oral therapeutic approach for enhanced management of inflammatory conditions.

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)